Heritability of insidious uveitis in Appaloosa horses. (9th October 2022) - Kingsley, Nicole B.; Sandmeyer, Lynne; Norton, Elaine M.; Speed, Doug; Dwyer, Ann; Lassaline, Mary; McCue, Molly; Bellone, Rebecca R.
Abstract: Equine recurrent uveitis (ERU) is a blinding ocular disorder among horses, and the Appaloosa horse breed is disproportionally affected by a chronic form of this intraocular inflammatory disease known as insidious uveitis. Strong breed predisposition and previous investigations suggest that there is a genetic component to the pathology of insidious uveitis among Appaloosa horses; however, no estimates of the heritability of the disease have previously been determined. This study aimed to characterize the genetic underpinning of the disease by estimating the heritability for insidious uveitis among Appaloosas. After combining two genotyping array datasets from the Illumina Equine SNP70 BeadChip and the Axiom Equine 670 K Genotyping Array, heritability was estimated for 59 affected and 83 unaffected horses using both restricted maximum likelihood (REML) and phenotype correlation – genotype correlation solvers from the linkage disequilibrium adjusted kinship software. Based on previous research, age and sex were used as covariates, and the locus responsible for the characteristic Appaloosa coat pattern (LP), previously associated with ERU risk, was included as a fixed effect ('top predictor'). Using prevalence values from 0.05 to 0.42, the heritability estimate for insidious uveitis ranged from 0.95 (SE = 0.14) to 1.74 (SE = 0.25) with LP contributing 0.16–0.33 to the estimate. This study suggests that insidious uveitis is highly heritable (REML 95% CI, h 2  = 0.68–1.0) and additional loci outside of LP are contributing to the genetic risk for insidious uveitis for Appaloosas. Once identified, these other genetic factors may lead to new disease mitigation efforts in veterinary care and breeding practices.